Extrusion-Cooking Techniques : Applications, Theory and Sustainability. - Moscicki, Leszek; Wiley InterScience (Online service) (Weinheim : Wiley-VCH, 2011)
Offering an engineering perspective plus the latest information on the application of this rapidly expanding technique, this practical book covers the technology, engineering, materials and products, as well as economic and ecological aspects. In addition to the theory, it also utilizes case studies that can easily be put into industrial practice. Each step of the process is discussed in terms of sustainability, and all data complies with the EU and FTA environmental regulations. Invaluable reading for food chemists and technologists, process engineers, chemists in industry, agricultural scien.
14 Thermoplastic Starch15 Scale-Up of Extrusion-Cooking in Single-Screw Extruders; 16 Producers of Food Extruders and Expanders; Index.
Print version record.
Includes bibliographical references and index.
Keywords: Extrusion process; Food processing machinery; Processed foods; Chemical engineering; Engineering; Food -- Extrusion; TECHNOLOGY & ENGINEERING -- Food Science; Chemical engineering; Engineering; Extrusion process; Food processing machinery; Processed foods; Electronic books